Psychometric Properties of the Workload scale in Ecuadorian Teachers - Méndez-Toledo, Franco Agustín (2022)
The objective of this research was to analyze the psychometric properties of the workload scale in Ecuadorian teachers. An instrumental design study was developed where data from 304 teachers of both sexes whose ages ranged from 20 to 60 years were analyzed. The confirmatory factor analysis showed that the internal structure of the workload scale is satisfactory ((χ2 = 28,147, df = 9, p = 0.01; CFI = 0.958; TLI = 0.931 and RMSEA = 0.080), evidence of convergent and discriminant validity was reached. Reliability is acceptable (α > 0.8). It is concluded that the workload scale in Ecuadorian teachers is a valid and reliable brief measure.